In Vitro Effect Of Malaysian Mikania Cordata Leaves Extract On Blood Coagulation Factors Level In Plasma - Yusoff, Nur Yuzaiza (2016)
Current anticoagulant agent such as warfarin and heparin have demonstrated lifethreatening side effect and its efficacy also been doubted. So, exploration of herbal plant been done and one of them is Mikania cordata